Biodegradation of petroleum hydrocarbon by indigenous bacteria isolated from Tarball at Terengganu beach, Malaysia - Martins, Nkem Bruno (2020)
Oil spills occur during exploration, production, vessel operation or accidents, discharge of industrial and municipal wastes. Spilled oil form Tarballs that are deposited on beaches. Oil spill triggers growth of oil-degrading bacteria which can be used for bioremediation by delivering sufficient nutrients and optimizing environmental conditions favorable for their growth. Petroleum pollution negatively impacts on human health, ecosystem and economy by causing birth defects, disrupting food chain, killing fishes and discouraging tourism. This study will aim to isolating and identifying indigenous hydrocarbondegrading bacteria from tarball in Terengganu Beach, Malaysia. Hydrocarbondegrading ability of isolated strains were compared to select the most efficient oil-degrading isolate. Diesel-oil biodegradation were optimized using single isolate and consortium of all isolated bacteria by Taguchi method. Biodegradation of diesel-oil was investigated using single most efficient isolate under optimized conditions on laboratory scale. Bioreactor was used to investigate diesel-oil biodegradation using consortium of isolated bacteria under optimized. Isolates were identified by biochemical characteristics and 16S rRNA gene sequence as Pseudomonas stutzeri DSM 5190, Cellulosimicrobium cellulans ATCC 12830, Acinetobacter baumannii CIP 70.34 and Pseudomonas balearica SP1402. All isolates are hydrocarbondegraders but C. cellulans exhibited maximum diesel-oil removal of 64.4% in 10 days. Taguchi optimization by C. cellulans generated maximum diesel-oil removal of 88.4% and optimal parameters were 2% (v/v) initial diesel concentration, 30.0 gL-1 NaCl concentration, 1.0 gL-1 NH4NO3 concentration, 7.0 pH, 40oC temperature, 100 rpm agitation speed and 14 days incubation time. However, combined effect of these parameters on diesel-oil degradation was not statistically significant with P > 0.05. Biodegradation of diesel-oil by C. cellulans recorded 94.6% diesel-oil removal under these optimized conditions after 30 days. The second Taguchi optimization by consortium generated maximum diesel-oil removal of 93.4%. Optimal parameters were 12% (v/v) initial diesel concentration, 40.0 gL-1 NaCl concentration, 1.0 gL-1 NH4NO3 concentration, 7.0 pH, 42oC temperature, 150 rpm agitation speed and 2.5 mL inoculum size. These parameters combined significantly to improve diesel-oil removal by 90.89% (R2) using consortium. Bioreactor treatment of diesel-oil using consortium of isolated bacteria removed 98.82% under optimized conditions after 60 days. Bioreactor parameters such as time (days), temperature, dissolved oxygen, pH and bacteria growth combined to significantly improve diesel-oil removal by 69.37% (R2). Treatment time (days) and bacteria growth were the most significant individual contributors to this improvement. Indigenous hydrocarbon-degraders isolated from tarball exhibited diesel-oil degradation potentials implying they can degrade several hydrocarbon pollutants. Taguchi design produced optimum parameter settings required to achieve the best biodegradation response within the shortest time. Bioreactor treatment using consortium was very effective because different parameters can be manipulated to optimal settings established using Taguchi approach, to achieve maximum bioremediation response. Results from this study can be used to develop unique bioremediation strategy for efficient decontamination of oil polluted sites in minimal time either ex situ using bioreactor, or in situ by direct application of consortium to contaminated sites.